PERENCANAAN KANTOR POLISI RESOR KONAWE UTARA DENGAN PENDEKATAN SMART BUILDING - Muhammad Yogi Saputra (GARIS Jurnal Mahasiswa Jurusan Arsitektur, 2022)
In order to realize and improve the service performance of the police apparatus in North Konawe district who have a high work ethic, so that they are able to serve the needs of the community. The demand for public services is increasing, therefore it is necessary to increase facilities and infrastructure that are able to accommodate all security activities in the North Konawe district government, considering that at this time the North Konawe Police Station is still holding development and improvement in terms of quantity and quality of buildings, infrastructure, and infrastructure. pre-suggestion facilities, so it is feared that it will reduce the morale of the security apparatus in this case the police at the North Konawe Police so that it ends up causing less than optimal work results in providing services to the community, which incidentally is a symbol and the main purpose of the presence of the Indonesian National Police institution, especially the District Police North Konawe. Departing from several forms of author anxiety that have been described above regarding the planning of the North Konawe Police Station. Then the author chooses a smart building approach which will later be applied to buildings. The choice of this approach is matched by the current vision of the Police, namely Precision. The author then began to try to form a concept about planning the shape of the building design and infrastructure of the North Konawe Police Office located in the Wanggudu sub-district, North Konawe district. Which then the author tries to compile in the form of a proposal with the title Planning of the North Konawe District Police Office With a Smart Building Approach